2000
DOI: 10.1097/00003072-200007000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Tc-99m Erythrocyte Localization of an Intramuscular Hemangioma of the Arm

Abstract: An unusual case of intramuscular hemangioma of the left triceps muscle is presented. This tumor may infiltrate the muscle and be misdiagnosed as a malignant neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Diagnostic imaging with Doppler imaging, MRI, angiography, and Tc-99m erythrocyte localization provides remarkable results. 3,4,16,17 In our study, US of the mass showed a large echogenic solid lesion in the anterior abdominal wall on the right side. This was followed by MRI with contrast showing a large intramuscular mass in the right anterior abdominal wall composed predominantly of adipose tissue with internal linear and nodular high T2 components showing minimal diffusion restriction and enhancement, which are highly suspicious for well-differentiated liposarcomas rather than lipomas.…”
Section: Outcome and Follow-upsupporting
confidence: 55%
See 1 more Smart Citation
“…Diagnostic imaging with Doppler imaging, MRI, angiography, and Tc-99m erythrocyte localization provides remarkable results. 3,4,16,17 In our study, US of the mass showed a large echogenic solid lesion in the anterior abdominal wall on the right side. This was followed by MRI with contrast showing a large intramuscular mass in the right anterior abdominal wall composed predominantly of adipose tissue with internal linear and nodular high T2 components showing minimal diffusion restriction and enhancement, which are highly suspicious for well-differentiated liposarcomas rather than lipomas.…”
Section: Outcome and Follow-upsupporting
confidence: 55%
“…Diagnostic imaging with Doppler imaging, MRI, angiography, and Tc‐99m erythrocyte localization provides remarkable results. 3 , 4 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%